Network Pharmacology and Molecular Docking-Based Investigation: Prunus mume Against Colorectal Cancer via Silencing RelA Expression - Minfeng Zhou; Jinxiao Li; Dan Luo; Haiming Zhang; Zhaomin Yu; Youlin Chen; Qiumeng Li; Fengxia Liang; Rui Chen (Frontiers Media S.A., 2021)
Colorectal cancer (CRC) is one of the most pervasive cancers in the human disease spectrum worldwide, ranked the second most common cause of cancer death by the end of 2020. Prunus mume (PM) is an essential traditional Chinese medicine for the adjuvant treatment of solid tumors, including CRC. In the current study, we utilize means of network pharmacology, molecular docking, and multilayer experimental verification to research mechanism. The five bioactive compounds and a total of eight critical differentially expressed genes are screened out using the bioinformatics approaches of Cytoscape software, String database, Gene Ontology analysis, Kyoto Encyclopedia of Genes and Genomes pathways, and molecular docking. RelA has been proven to be highly expressed in CRC. Experiments in vitro have shown that kaempferol, the main active component of PM, dramatically inhibited the growth, migration, and invasion of CRC cells, and experiments in vivo have shown that PM effectively delays CRC formation and improves the survival cycle of mice. Further analysis shows that PM inhibits the CRC progression by down-regulating the expression level of RelA, Bax, caspase 3, caspase 9, and EGFR in CRC. PM and its extract are potentially effective therapeutics for the treatment of CRC via the RelA/nuclear factor κB signaling pathway.